Improving Students’ Learning Achievement Of Science On Describing The Natures Of Light Using Demonstration And Experiment Method (Demex) For The Fifth Grader Of B Group In Sdn 1 Karanganyar - Priyanti, Priyanti (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2014)
The study was aimed at improving the students’ learning motivation and achievement of science on “Describing the natures of light” applying two methods of demonstration and experiment. This involved the students’ active participation in group works. It applied a classroom action research conducted following the principles of Kemmis S, C Taggart R (1988) covering planning, acting, oberserving, and reflecting or evaluating. These stages were done to achieve the improvement target in two cycles. This was done by collaborating with the peers as observer, supervisor and the principal of the elementary school, in the Education District Unit of Karanganyar, Purbalingga Regency. Based on the analysis, it can concluded that (1) the students’ participation and understanding is better; they are motivated better and actively involved in the learning activities, (2) the students’ learning achievement also improves, using this method. After the cycle I, the students’ learning mastery was 53,12%, with an average score of 68,91 and their motivation index was 71,88%. At the end of the cycle II, their mastery increased significantly, 81,25%, and their average score was 78,13. Their motivation improved to 84,38%. The results of the cycle II has shown that their mastery level has exceeded the target to be more than 75% and also their learning motivation. Based on the findings, it can be concluded that the use of Demex method in science learning of describing the natures of light is effective in this research.